2021
DOI: 10.1016/j.dcn.2021.100927
|View full text |Cite
|
Sign up to set email alerts
|

The development of brain functional connectome during text reading

Abstract: Reading is an important skill for human beings to obtain information, whose acquisition is a major learning task for children. Especially, compared with single word reading, text reading requires an integration of multiple cognitive processes, which makes its underlying neural developmental mechanism not only extremely complicated but also remained poorly understood. Employing the graph theory analysis method, the present study explored the development of brain in the context of story reading from the perspect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 56 publications
1
16
0
Order By: Relevance
“…Chinese characters that are also used in Japanese writing as kanji represent meaning in addition to pronunciation. This difference indeed seems reflected by the developmental shift of the areas activated by reading from the auditory network in comparison to the visual network ( Zhou et al, 2021 ). The stimulation may be more effective when it is provided to the areas outside of the auditory association cortices for those who write using Chinese characters.…”
Section: Discussionmentioning
confidence: 99%
“…Chinese characters that are also used in Japanese writing as kanji represent meaning in addition to pronunciation. This difference indeed seems reflected by the developmental shift of the areas activated by reading from the auditory network in comparison to the visual network ( Zhou et al, 2021 ). The stimulation may be more effective when it is provided to the areas outside of the auditory association cortices for those who write using Chinese characters.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the involvement of the DMN in the frequency effect may arise from the level of semantic memory (Almeida et al, 2007;Bonin & Fayol, 2002). Previous studies have shown that adults exhibit greater FC between visual-related and semantic-related brain regions and decreased connectivity in phonological information networks when reading in Chinese (Zhou et al, 2021). Therefore, the link between the frequency effect and connectivity within the DMN in adults is not surprising because the semantic activation of characters is more efficient and sufficient in adults than in children, which leads to the high possibility that semantic information cascades into motor processes involved in handwriting.…”
Section: Discussionmentioning
confidence: 99%
“…Beginning readers often rely extensively on letter‐to‐sound processing, but with experience they learn to integrate visual and semantic processing (Zhou et al., 2021). As they gain experience with written words, readers can retrieve word meanings more directly and establish brain systems for mapping whole words to meaning (Eddy et al., 2014).…”
Section: Two Research‐based Stories: a Confluence Of Complexitymentioning
confidence: 99%